Dampak Optimalisasi Kesehatan Remaja dengan Edukasi Bijak Dalam Penggunaan Obat Kepada Siswa SMP - Marfuati, Sri; Weni, Mustika; Brajawikalpa, Rama Samara; Emallia Fitriani (JPM: Jurnal Pengabdian Masyarakat, 2025)
Self-medication is increasingly common among the general public, including adolescents. However, a lack of proper understanding regarding drug use, storage, and disposal can lead to medication errors that pose serious health risks. This community service activity aimed to improve the knowledge of students at SMP regarding the proper and responsible use of medications through an educational session titled “Using Medicines Wisely.” The activity was conducted on May 24, 2025, by lecturers from the Faculty of Medicine, Universitas Swadaya Gunung Jati (UGJ), using a face-to-face method involving a pre-test, educational material delivery, interactive discussion, and a post-test. Pre-test results showed that only 22% of participants had good knowledge, which increased to 68% after the educational session with the meaning of value. These findings indicate that the activity effectively enhanced students’ understanding of responsible self-medication practices, particularly in recognizing drug types, usage instructions, proper storage, and safe disposal methods. This program is expected to foster wise medication habits from an early age and contribute to the development of a health-conscious society.